Tricked ebook The iron druid chronicles, book four. - Hearne, Kevin (Iron Druid Chronicles, 2012)
Druid Atticus O’Sullivan hasn’t stayed alive for more than two millennia without a fair bit of Celtic cunning. So when vengeful thunder gods come Norse by Southwest looking for payback, Atticus, with a little help from the Navajo trickster god Coyote, lets them think that they’ve chopped up his body in the Arizona desert. But the mischievous Coyote is not above a little sleight of paw, and Atticus soon finds that he’s been duped into battling bloodthirsty desert shapeshifters called skinwalkers. Just when the Druid thinks he’s got a handle on all the duplicity, betrayal comes from an unlikely source. If Atticus survives this time, he vows he won’t be fooled again. Famous last words. Don’t miss any of Kevin Hearne’s phenomenal Iron Druid Chronicles novels: HOUNDED | HEXED | HAMMERED | TRICKED | TRAPPED | HUNTED | SHATTERED | STAKED